Serum Biomarkers in Breast Cancer: A Comparative Study of Xanthine Oxidase, Thymidine Kinase, and Hormonal Profiles in Iraqi Women - Sami Khlaif Mansoor (American Journal of Biomedicine and Pharmacy, 2025)
The "study was conducted in the laboratories of Marjan Teaching Hospital and several private laboratories in the city of Hilla, Babylon Governorate, from December 1, 2023, to January 15, 2024. It included 35 samples from women with breast cancer, aged between 35 and 70 years, and 35 samples from healthy women of the same age range, serving as control samples. The breast cancer diagnoses were confirmed by specialists at the Cancer Center. Blood samples were collected from both groups (patients and controls) and separated using centrifugation. The levels of xanthine oxidase (XO), thymidine kinase-1 (TK1), and various variables, including CRP, estrogen, progesterone, vitamin D, iron, and calcium, were then measured. The results of the study demonstrated a significant increase in the levels of XO, TK1, CRP, progesterone, estrogen, iron, and calcium, and a significant decrease in vitamin D levels in the blood serum of the breast cancer group compared to the control group, with a statistical significance of P ≤ 0.001. This study highlights the significant biochemical differences between breast cancer patients and healthy individuals, suggesting that these biomarkers could potentially be useful for the diagnosis and monitoring of breast cancer. Further research is warranted to explore the underlying mechanisms of these changes and their implications for breast cancer prognosis" and therapy.